Assessment of Compliance with Contact Lens Wear and Care Among University-Based Population in Iraq - Abeer Imad Aldahhan; Salah Zuhair Al-Asadi (مجلة الكوفة الطبية)
Purpose: The aim of the study is to assess the compliance level with the wear of contact lens in a sample of students in Iraq. Methods: A self-administered questionnaire1 was used to collect data from the designated respondents group. The questionnaire consisted of 34 questions that cover 5 main subjects, these are: general information, usage, care, hygiene and storage. Results: There were 400 students that participated in the study. Of the study population 36 (9.0 %) were males and 364 (91 %) were females. The average age of the research participants was 22.8 (± 3.7). The study population had a high compliance rate of 31.25 % on 5 behaviours, these are: not sleep while wearing, not showering while wearing, not using saliva to clear, removing when eye gets red and not sharing lens case with friends. Moderate level of compliance rate was 56.25 % and reported in the following aspects: not sharing between users, not overuse solution after its expiry, not using water to clean, clean lens after its removal, adherence to instruction of cleaning, soaking more than 4 hours a night, checking for damage and hand washing before using. However, low levels of compliance rate were 12.5 % and reported in: not rubbing lens with fingers and cleaning and rinsing lens case. Conclusion: Participants indicated high to moderate compliance. It is advised, however, that improved strategies be used in order to further raise levels of compliance among Iraqi university students who wear contact lenses. Even though this study focuses on university students who use contact lenses, a larger sample of contact lens wearers from the general lay population is suggested to be investigated in future.